Possible Involvement of 5-Lipoxygenase Metabolite in Itch-Associated Response of Mosquito Allergy in Mice - Yasushi Kuraishi; Eiji Ohtsuka; Tasuku Nakano; Sanae Kawai; Tsugunobu Andoh; Hiroshi Nojima; Kiyoshi Kamimura (Elsevier, 2007)
This study investigated endogenous mediators involved in mosquito allergy-associated itching in mice. An intradermal injection of an extract of mosquito salivary gland elicited marked scratching in sensitized mice. The 5-lipoxygenase inhibitor zileuton (100 mg/kg), the 5-lipoxygenase activating peptide inhibitor MK-886 (10 mg/kg), and the glucocorticoid betamethasone 17-valerate (3 mg/kg) inhibited the scratching. The scratching was not affected by the cyclooxygenase inhibitors indomethacin and ketoprofen, the TP prostanoid receptor antagonist SQ-29548, the leukotriene B4 antagonist ONO-4057, the cysteinyl leukotriene antagonist pranlucast, the leukotriene D4 antagonist MK-571, the platelet-activating factor antagonist CV-3988, the nitric oxide synthase inhibitor NG-nitro-L-arginine methyl ester, the H2 histamine-receptor antagonist cimetidine, the H1 histamine-receptor antagonist terfenadine plus cimetidine, and cypoheptadine that blocks the 5-HT1/2 serotonin receptors. Zileuton (100 mg/kg) inhibited the increased activity of the cutaneous nerve branch induced by an intradermal injection of the extract, suggesting the peripheral action. Zileuton and MK-886 (10 and 100 µM) did not affect high K+-induced increase in intracellular Ca2+ concentration in cultured dorsal root ganglion neurons. The results suggest that 5-lipoxygenase metabolite(s) other than leukotriene B4 and cysteinyl leukotrienes are involved in mosquito allergy-associated itching. Keywords:: itch of mosquito allergy, 5-lipoxygense metabolite, zileuton, cutaneous nerve branch, dorsal root ganglion neuron